Differentiated use of auxiliary projectiles in the preparation of high-class javelin throwers based on the consideration of biomechanical features of the implementation of the final effort - Abakumova, M. V.; Chermit, K. D.; Zabolotny, A. G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate and experimentally test the methodological conditions for the shared use of auxiliary projectiles in the preparation of high-class javelin throwers.